Agrobacterium-mediated genetic transformation of the most widely cultivated superior clone Eucalyptus urophylla × Eucalyptus grandis DH32-29 in Southern China - Wang, Xiaoping; Chen, Shanshan; Zhang, Haonan; Luo, Ping; Zhou, Fangping; Zeng, Bingshan; Xu, Jianmin; Fan, Chunjie (Frontiers in Plant Science, 2022)
Eucalyptus, as an economically important species for wood and paper industries, still remains a challenge to genetic improvement by transgenic technology owing to the deficiency of a highly efficient and stable genetic transformation system, especially in cultivated superior clones. Eucalyptus urophylla × E. grandis clone DH32-29 is most widely planted in southern China, but it is relatively recalcitrant to adventitious bud regeneration, which blocks the establishment of a genetic transformation system. Here, an efficient adventitious bud regeneration and transformation system of Eucalyptus was established using E. urophylla × E. grandis DH32-29 as material. The in vitro leaves from microshoots that were subcultured for 20-25 days were immersed into liquid Woody Plant Medium supplemented with 0.02 mg·L-1 α-naphthaleneacetic acid (NAA) and 0.24 mg·L-1 forchlorfenuron (callus-inducing medium, CIM). After 15 days, explants were transferred to a medium containing 0.10 mg·L-1 NAA and 0.50 mg·L-1 6-benzyladenine (shoot-inducing medium, SIM) for adventitious bud induction. The highest regeneration efficiency of adventitious buds was 76.5%. Therefore, an Agrobacterium tumefaciens-mediated genetic transformation system was optimized. The leaves were precultured for 7 days and infected for 30 min with A. tumefaciens strain EHA105 grown to a bacterial density of 0.3 (OD600). After 72 h of cocultivation in the dark, leaves were transferred to CIM supplemented with 100 mg·L-1 cefotaxime (Cef), 100 mg·L-1 timentin, and 15 mg·L-1 kanamycin (Kan) for 15 days to induce calluses. Then, the explants were transferred to SIM supplemented with the same concentration of antibiotics, and the fresh medium was replaced every 15 days until resistant adventitious buds appeared. After inducing roots in root-inducing medium supplemented with 200 mg·L-1 Cef and 75 mg·L-1 Kan, completely transgenic plants were obtained. Using the aforementioned method, the transformation frequency can reach 1.9%. This provides a powerful approach for genetic improvement of E. urophylla × E. grandis DH32-29 and gene function analysis in Eucalyptus.